2020
DOI: 10.3389/fonc.2020.01738
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Laparoscopies and Laparotomies for Radical Hysterectomy in Stage IA1-IB1 Cervical Cancer Patients: A Single Team With 18 Years of Experience

Abstract: Objective To investigate the safety and efficacy of abdominal radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH) in managing early-stage cervical cancer. Methods This retrospective study comprised patients with FIGO stage IA1 with lymphovascular space invasion (LVSI), IA2, and IB1 cervical cancer who underwent radical hysterectomy performed by a single gynecologic oncology team at Peking Union Medical College Hospital from 2000–2018. The clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…In this study, patients with cervical cancer who underwent MLRH by Dr. Songhua Yuan had a satisfactory prognosis, and the 5‐year DFS and OS were comparable with those of open surgery, as reported in the Laparoscopic Approach to Cervical Cancer Trial (5‐year DFS, 94.5% vs. 96.5%; 5‐year OS, 96.7% vs. 97.6%) 2 . Some studies reported 5‐year DFS and OS of 89.3%–97.7% and 95.2%–99.4%, respectively, in patients with early stage cervical cancer by laparotomy 19–21 . The long‐term prognoses of the patients in our study who underwent MLRH were not inferior to those described in the above studies.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, patients with cervical cancer who underwent MLRH by Dr. Songhua Yuan had a satisfactory prognosis, and the 5‐year DFS and OS were comparable with those of open surgery, as reported in the Laparoscopic Approach to Cervical Cancer Trial (5‐year DFS, 94.5% vs. 96.5%; 5‐year OS, 96.7% vs. 97.6%) 2 . Some studies reported 5‐year DFS and OS of 89.3%–97.7% and 95.2%–99.4%, respectively, in patients with early stage cervical cancer by laparotomy 19–21 . The long‐term prognoses of the patients in our study who underwent MLRH were not inferior to those described in the above studies.…”
Section: Discussionsupporting
confidence: 70%
“…18 Furthermore, CO 2 pneumoperitoneum has been found to promote tumor cell growth or spread in cell-culture and animal trials. [19][20][21] The long-term prognoses of the patients in our study who underwent MLRH were not inferior to those described in the above studies. Moreover, several studies with high levels of evidence have revealed that laparoscopic surgery is not inferior to open surgery in patients with gastric or colorectal cancer in terms of long-term survival.…”
Section: Discussionsupporting
confidence: 46%
“…Table 1 presents the characteristics of the included studies. All 30 studies 8,14,15,18,23–48 were retrospective cohort studies. Two studies involved comparisons among three groups, including LRH versus ORH versus LVRH, and RRH versus LRH versus ORH; the remaining 28 studies compared two groups, LRH versus ORH (14 studies), RRH versus ORH (6 studies), VALRH versus ORH (4 studies), and LRH versus RRH (4 studies).…”
Section: Resultsmentioning
confidence: 99%
“…By reading the full texts, 32 articles were further excluded because 10 among them had patients with FIGO Stage IIb, while 15 did not discuss the main study outcome and 7 involved duplicate data. Finally, 22 retrospective studies in keeping with the inclusion criteria were selected for analysis 2,7–11,13–28 . The literature screening process is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 22 retrospective studies in keeping with the inclusion criteria were selected for analysis. 2,[7][8][9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The literature screening process is illustrated in Figure 1.…”
Section: Results Of Searching For Studiesmentioning
confidence: 99%